## Solving the Equation: (x) + (x+3) + (x-2) + 3(x+3) - 1 = 87

This article will guide you through the process of solving the equation (x) + (x+3) + (x-2) + 3(x+3) - 1 = 87.

### Step 1: Simplify the Equation

First, we need to simplify the equation by combining like terms.

**Distribute the 3:**3(x+3) = 3x + 9**Combine x terms:**x + x + x + 3x = 6x**Combine constant terms:**3 - 2 + 9 - 1 = 9

The simplified equation is now: **6x + 9 = 87**

### Step 2: Isolate the Variable

To isolate the variable 'x', we need to get rid of the constant term (+9). We can do this by subtracting 9 from both sides of the equation:

**6x + 9 - 9 = 87 - 9****6x = 78**

### Step 3: Solve for x

Now, we have 6x = 78. To find the value of x, we need to divide both sides of the equation by 6:

**6x / 6 = 78 / 6****x = 13**

### Solution

Therefore, the solution to the equation (x) + (x+3) + (x-2) + 3(x+3) - 1 = 87 is **x = 13**.